Shamanic regalia in the far north - Anawalt, Patricia Rieff (London Thames & Hudson, 2014)
Probes into the significance and meaning of shamanic practices in Northeast Siberia, Alaska and British Columbia, and also points up the intriguing differences in the ritual garb as generation after generation sought to influence events through the aid of spirits.
Introduction -- Siberia -- The Arctic and Alaska: Eskimo -- The Tlingit of the Northwest Coast
Includes bibliographical references (pages 174 - 176) and index.
Keywords: Shamanism -- Arctic regions; Shamanism -- History; Regalia -- Arctic regions; Religious articles -- Arctic regions; Arctic peoples -- Clothing; Arctic peoples -- Material culture; Eskimos -- Religion; Tlingit Indians -- Religion